Mother-reported sleep, accelerometer-estimated sleep, and weight status in Mexican American children: Sleep duration is associated with increased adiposity and risk for overweight/obese status - Martinez, Suzanna M. (J Sleep Res, 2013)
We know of no studies comparing parent-reported sleep with accelerometer-estimated sleep in their relation to pediatric adiposity. We examined: 1) the reliability of mother-reported sleep compared with accelerometer-estimated sleep, and 2) the relationship between both sleep measures and child adiposity. The current cross-sectional study included 304 Mexican American mother-child pairs recruited from Kaiser Permanente Northern California. We measured sleep duration, using maternal report and accelerometry, and child anthropometrics. Concordance between sleep measures was evaluated using the Bland-Altman method. We conducted zero-ordered correlations between mother-reported sleep, accelerometer-estimated sleep and child BMI z-scores (BMIz). Using linear regression, we examined three models to assess child BMIz with mother-reported sleep (model 1), accelerometer-estimated sleep (model 2), and both sleep measures (model 3). Children had an average age of 8.86 years (SD= .82). Mothers reported that their child slept 9.81 ± 0.74 (95% CI: 9.72, 9.89) hours, compared to 9.58 ± 0.71 (95% CI: 9.50, 9.66) hours based on accelerometry. Mother-reported sleep and accelerometer-estimated sleep were correlated (r = 0.33, p < 0.001). BMIz outcomes were negatively associated with mother-reported sleep duration (model 1: β = −0.13; P = .02) and accelerometer-estimated sleep duration (model 2: β = −0.17; P < .01). Accounting for both sleep measures, only accelerometer-measured sleep was related to BMIz (model 3: β = −0.14, P = .02). Each sleep measure was significantly related to adiposity, independent of covariates. Accelerometry appeared to be a more reliable measure of children’s sleep than maternal report, yet maternal report may be sufficient to examine the sleep-adiposity relationship when resources are limited.